Appropriation of adaptive literacy games into the German elementary school classroom. (23rd July 2021) - Pflaumer, Nadine; Knorr, Nancy; Berkling, Kay
Abstract: The study presented here was aimed at understanding how teachers go about appropriating technology from the iRead EU Horizon 2020 Project into the classroom. iRead provides an adaptive personalised literacy game called Navigo that is deployed in tablets and intended for regular usage in the elementary school classroom. In our case, the game was provided for beginning readers of German. The goal of iRead was to develop these games and then understand how these can be deployed successfully into the classroom. The adaptation of technology by teachers has been a well‐studied phenomenon for decades in some countries. However, in Germany, elementary schools lag behind in digitalisation, making such studies more difficult, resulting in a knowledge gap this study seeks to fill. Appropriation of the Navigo game by the teachers was studied through a series of semi‐formal interviews with 21 teachers from 9 schools, scheduled at the beginning, middle and end of the project, resulting in a total of 55 interviews. Results show that teachers had similar experiences within the project, and faced common stumbling blocks, such as (a) technology, (b) digital literacy and (c) understanding the pedagogical use of adaptive learning games. While teachers generally accepted that interacting with tablets taught pupils the important skill of digital literacy, most teachers did not fully understand how pupils acquired language skills through Navigo. Those teachers who understood the academic benefit of the learning game appropriated Navigo fully by purposefully leveraging the adaptivity of the games to support pupils in a personalised manner. Using thematic analysis and automatic clustering of keyword occurrences in the interviews, we were able to identify four 'personas' on the continuum of teacher characteristics. Mapping teachers to these 'personas' determined the level of support required during the appropriation process. It was shown that the 'personas' are relatively stable and can be identified within the first weeks of appropriation to ensure a successful process as soon as possible. Practitioner notes What is already known about this topic Appropriation of technology models. Technology use in school for older pupils. Educational games outside of school. What this paper adds A view on technology usage in elementary schools particular to the German context with large amount of teacher interviews from diverse schools. Personas that can be identified early on in the process of appropriation based on simple interviews. Particular challenges of using adaptive technology in the classroom. Implications for practice and/or policy A simple model for picking appropriate teacher support in appropriation. Results show a clear need for improving technology support in the schools. Teacher training must include digital competence and openness to the idea of independent learning paths.